2001
DOI: 10.1525/mp.2001.19.1.121
|View full text |Cite
|
Sign up to set email alerts
|

A Rule of Thumb: The Bandwidth for Timbre Invariance Is One Octave

Abstract: Listeners were unable to determine whether two different notes separated by an octave or more were played by the identical or a different wind instrument and similarly were unable to determine whether a vowel sung at different pitches separated by an octave or more was sung by the identical or a different soprano or mezzo-soprano.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 6 publications
2
29
0
1
Order By: Relevance
“…This is consistent with previous research suggesting that the bandwidth of timbre invariance between objects with similar methods of excitation is around 1 octave. 5 The findings presented in Table 2 FIGURE 1. User interface with written instructions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with previous research suggesting that the bandwidth of timbre invariance between objects with similar methods of excitation is around 1 octave. 5 The findings presented in Table 2 FIGURE 1. User interface with written instructions.…”
Section: Resultsmentioning
confidence: 95%
“…Based on their work with instruments, 4,5 Erickson et al have engaged in a series of studies designed to test how listeners use timbre to identify or discriminate singers. Using female voices and a three-note oddball task, Erickson et al 6 found that when comparison intervals exceeded 1 octave, inexperienced and experienced listeners were unable to detect the different singer within or across voice category and most often chose the most dissimilarly pitched stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible interpretation for the reliance of material identification on sound frequency is more subtle. Studies on the perception of musical timbre show that the influence of pitch on judgments of the dissimilarity of musical timbres grows with the range of variation of pitch within the experimental set and, in particular, becomes relevant at the expense of a focus on non-pitch acoustical information when participants are exposed to pitch variations larger than one octave (Handel and Erickson 2001;Marozeau et al 2003;Steele and Williams 2006). Accordingly, the reliance of material identification on frequency observed in previous studies was determined by the comparatively large variation of this pitchrelated acoustical variable (e.g.…”
Section: Perception Of Stiff Solid Materialsmentioning
confidence: 99%
“…A model of sound production influential on the theory of timbre perception is the source-filter model by Handel (1989Handel ( , 1995Handel ( , 2006see Fant, 1960, for the speechproduction antecedent of this theory). Accordingly, a musical tone is the product of the interaction between a source (e.g., a vibrating object such as the string in a violin) and a filter (e.g., the violin body) that selectively amplifies and suppresses different frequencies of the mechanical vibration of the source and radiates the sound.…”
Section: T H E S C I E N T I F I C S T U D Y O F M U S I C a L T I M mentioning
confidence: 99%